Pengorganisasian Personil Kepengurusan Pondok Pesantren Fathul Ulum Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Muhammad Sanusi; Ahmad Ridwan; Sodiah Sodiah; Zumratul Khairiyah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
Leaders of Islamic Boarding Schools are people who have great influence in a boarding school. As a manager the principal plays a role in managing the educational resources they have. The school principal must be able to bring change to the school he leads to become a quality school by utilizing resources, especially teachers. Teachers are required to master pedagogic, professional, social, and personality competencies, for this reason the real role of the school principal is needed to improve teacher competence. This study uses a qualitative approach. This study aims to identify and describe the role of the principal as a manager in implementing strategies through collaboration and communication at the Fathul Ulum Islamic Boarding School, Tebing Tinggi District, Tanjung Jabung Barat District in terms of Planning, Organizing, Actuating aspects. , Controlling (Supervision), as well as the efforts made by the principal in improving the competence of teachers at the Fathul Ulum Islamic Boarding School which includes; school principals' support for teacher competency improvement programs; and facilities provided in an effort to increase teacher competence. The results of this study are that the leadership of the Fathul Ulum Islamic Boarding School has carried out its role as a manager by carrying out management principles which include Planning, Organizing, Actuating, Controlling. Planning (Planning) is carried out by the principal by drafting a school program based on the foundation's policy. Organizing is done by dividing the tasks to each school personnel to jointly run the program that has been made. Actuating (Motivating) is the principal's activity to move each personnel to consciously support the program being run. While Controlling (Supervision) is an activity carried out by the principal to determine the success of the program that has been implemented. The leadership of the Fathul Ulum Islamic Boarding School has provided full support for the teacher competency improvement program by providing opportunities for teachers to continue their studies and involving teachers in various trainings, workshops, and also training. The school principal facilitates the needs of teachers in an effort to increase teacher competence by providing scholarships to teachers to carry out further studies, allowances and other educational facilities.